Functional performance tests, on-ice testing and game performance in elite junior ice hockey players - Daigle, A.-P.; Bélanger, S.; Brunelle, J.-F.; Lemoyne, J. 1,2 (Journal of Human Kinetics, 2022)
This study aimed to explore relationships between fitness, on-ice physical abilities and game performance among elite junior male ice hockey players. Twenty-one major junior ice hockey players (18.9 ± 1.4 years old) participated in the study. Measures including five fitness tests (anthropometric measures, pull up test, bench press test, broad jump, vertical jump) and three on-ice skating tests (multi-stage aerobic skating test, 44-m sprint test, and backward skating test) were assessed during their pre-season training camp. Game performance metrics (collected during the regular season) were collected using InStat software. Results of the (on-ice and off-ice) functional performance test protocol and on-ice tests were analyzed by evaluating correlation coefficients in multiple areas of game performance: 1) physical implication (body checks), 2) offensive contribution (expected goals for, types of zone entries), and 3) defensive actions (blocked shots, expected goals against). They revealed that performance in the broad jump test was associated with skating speed. Some significant correlations were also observed between on-ice test performance indicators such as received body checks, expected goals and blocked shots. In summary, results indicate that on-ice test protocols were associated with players` performance in multiple aspects of the game. Partial correlation analyses revealed that some of these relationships were specific to the player's position. Forward skating was associated with forwards` offensive play, and backward skating was specifically related with defensemen`s performance (offense and defense). The addition of on-ice physical tests appears essential for interpreting the results of ice hockey players' physical tests and integrating these results into players` physical preparation and the in-season follow-up.